The Department of Education's (WA) Rural and Remote Training Schools Program - Lobb, Richard (Australian and International Journal of Rural Education, 2019)
The Department of Education initiated a pilot of the Rural and Remote Training Schools project in 2011 to promote rural and remote teaching to university students. The program is a key component of the Department's broader attraction and retention strategy and targets the Pilbara, Kimberley, Midwest and Goldfields regions; areas that are deemed to be difficult to staff. Attraction and retention of quality teachers in rural and remote locations remain key Departmental priorities. A key component of the program involves the manager working closely with Universities to promote the program and to identify high performing pre-service teachers who are interested in undertaking a long term (usually final) practicum in a rural or remote school. The manager also works with schools, regional offices and mentor teachers to ensure that the required conditions are in place within each school to provide the pre-service teacher with a supportive 'training' environment.